Realizing the principle of simple, fast, and low cost in civil dispute examination with the e-Court application model - Dudung Hidayat (Al-Makki Publisher, 2023)
The influence of technological developments on the case examination process is in line with the industrial revolution which requires the application of technology-based performance, which is used in administering cases and implementing procedural law. The online system is a new breakthrough in the administration of justice. The formulation of the problem is how to apply e-court in the examination of cases in the Court, and how the application of the principle of simple, fast, and light costs is connected with e-court in the Court. The purpose of this study is to find out how the application of e-court in the examination of cases in the Court, as well as to find out how the application of the principle of simple, fast, and light costs when connected with e-court in the Court. The method used is empirical juridical. The results of the study, the application of e-court in case examination, namely for online case registration, obtaining online case cost estimates, online payments, electronic summons, and electronic trials. E-court can be accessed by registered users and other users. E-court as a case administration management system is very helpful for the mechanism of proceedings in court because it simplifies and speeds up the stages of registration and examination in court, in addition to the registration, summons, and submission of hearing documents are carried out electronically so as to save costs.